Superbugs-related prolonged admissions in three tertiary hospitals, Kano State, Nigeria - Alkali, Bashir; Garba, Iliyasu; Adamu, Almustapha Aliero; Abdurrazak, Kibiya; Muhammad, Hassan Abubakar; Ibrahim, Ntulume; Faruku, Sarkinfada; Ezera, Agwu (The Pan African Medical Journal., 2019)
Introduction: Superbugs are pathogenic microorganism and especially a bacterium that has developed resistance to the medications normally used against it. As the superbug family increases, the need for appropriate diagnostic, treatment, prevention and control strategies cannot be over emphasized. Therefore, this work determined the distribution of superbug bacteria among patients on prolonged hospital admissions in three tertiary hospitals of Kano state, Nigeria. Methods: A descriptive cross sectional study was undertaken among 401 patients from medical, surgery, orthopedic and burn Centre wards in a three tertiary hospitals in Kano state. A sample collected comprises wound/pus, urine, urine catheter and nasal intubation and were analysed using standard microbiological methods for Acinetobacter spp and other related nosocomial bacterial pathogens. Antibiotic susceptibility testing was done using Kirby-Bauer disc diffusion method. Results: One hundred and thirty eight (138) isolates were recovered, from the studied participants. More than 80% of the nosocomial infections (Nis) were caused by Gram-negative bacteria, predominantly Escherichia coli, Klebseilla spp, Proteus spp, Pseudomona spp, and Acinetobacter spp. In-vitro antibiotic susceptibility test revealed that Acinetobacter were 100% resistant to Amoxicillin, Co-trimoxazole, Perfloxacin and Imipenem. Conclusion: The results of this study reported higher antibiotic resistant among Acinetobacter spp isolated from three studied hospitals. The healthcare manage of the these hospitals and ministry health need to take measures against this resistant bacteria (Acinetobacter spp) especially on prescribing antibiotics that showed 100% resistant from these studied hospitals.